MUNICIPALITIES: OPPORTUNITIES TO IMPROVE FINANCIAL SECURITY - Blazhevich, Oleg; Burkaltseva, Diana; Shalneva, Vlasta; Smirnova, Elena; Guk, Olga; Kirilchuk, Nadezhda; Safonova, Natalia; Daudov, Ibragim; Gadayeva, Kheda (Revista Inclusiones, 2019)
Among the elements that make up the financial security of the state, a special place belongs to the financial security of municipalities, as the foundation of general financial security. In connection with the foregoing, the purpose of the article is to determine the methodology for assessing the financial security of municipalities. The article substantiates the main stages of assessing the financial security of municipalities, including collecting baseline information, grouping and calculating statistical indicators, bringing them into a comparable form, calculating the integrated indicators of financial security for each municipality, assessing the financial security of municipalities and the distribution of municipalities by levels of financial security. It has been concluded that using the proposed methodology allows the following: comparing the levels of financial security of various municipalities in the region, identifying lags in specific groups of indicators for each municipality and calculating financial security at the regional level as a whole.